Status and influencing factors of activities of daily living among rural elderly people in western Yunnan province: a cross-sectional survey - Shuqing LIU; Xuehui ZHANG; Yulin ZHANG; Nishang ZHANG; Yahui XU; Liudan LI; Jiaxiang YIN; Rudan HONG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the status and influencing factors of activities of daily living (ADL) among rural elderly people in western Yunnan and to provide evidence for making policies on improving quality of life in the elderly. MethodsThe participants of the survey were 2 287 adult permanent residents ( \begin{document}$\geqslant $\end{document} 60 years old) recruited with multistage random cluster sampling in rural regions of western Yunnan province. Face-to-face interview, physical examination and bone density test were conducted among the participants during July - August 2021. Chinese version scales including Physical Self-maintenance Scale (PSMS)，Instrumental Activities of Daily Living Scale (IADL)，2-Item Patient Health Questionnaire (PHQ-2)，and 2-Item Generalized Anxiety Disorder (GAD-2) were adopted in the survey. Amos 26.0 statistical software was used to build structural equation models for analysis on influencing factors of ADL in the rural elderly. ResultsValid information were collected from all the participants. The proportions of participants identified as with overall, instrumental, and physical ADL impairment were 30.74%, 24.70%, and 10.80%, respectively, with 13.95% and 10.06% of the participants reporting difficulty in cell phone use and walking. The results of structural equation model analysis showed that physiological factors had direct effects on ADL (β = 0.20)；lifestyle had direct effect on ADL (β = 0.13) and indirect effect through physiological factors (β = 0.01)；psychological factors had direct effects on ADL (β = 0.09)；socio-economic factors have direct effects on ADL (β = 0.08) and indirect effects through lifestyle (β = 0.01)；social support has no direct effects on ADL but had indirect effects through psychological factors (β = 0.01). ConclusionThe prevalence of ADL impairment was relatively high and interactively influenced by physiological, psychological, and socio-economic factors and by lifestyle and social support among rural elderly in western Yunnan province. The results need to be concerned in developing interventions on ADL impairment in the population.